A comparative analysis of the Flutter and React Native frameworks - Markowski, Mateusz; Smołka, Jakub (Journal of Computer Sciences Institute, 2023)
The article describes a comparative analysis of the resource usage performance of mobile applications developed using Flutter and React Native frameworks. The purpose of this study was to see which technology is more efficient. The study consisted in creating two mobile apps with the same functionalities and then comparing usage of the following resources: Virtual Memory (VIRT), Shared Memory (SHR), Central Processing Unit (CPU), Resident Set Size (RES) and Memory (MEM). The functionality of the application consisted of actions on the GUI. The test was conducted on a Huawei P20 Lite smartphone, using the Android Debug Bridge (ADB) tool and custom scripts in the Bash shell language. The results do not clearly indicate which technology is more efficient.